The The Influence of Business Capital and Financial Management on the Financial Performance of MSMEs (Case Study of Culinary MSMEs in Asia Mega Mas Medan): Pengaruh Modal Usaha dan Pengelolaan Keuangan Terhadap Kinerja Keuangan UMKM (Studi Kasus Pada UMKM Kuliner di Asia Mega Mas Medan) - Sony; Susan Grace V. Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to determine whether Business Capital and Financial Management have a significant effect on the Financial Performance of Culinary MSMEs in Asia Mega Mas Medan. This study uses quantitative data methods and the data source is primary data. The population in this study is all Culinary MSMEs. The sample of this study was 66 Culinary MSMEs obtained by purposive sampling technique. Data analysis and testing include validity test, reliability tests, descriptive statistics, classical assumption tests, multiple regression analysis, partial hypothesis testing (T test) and simultaneous hypothesis testing (F test), and determination coefficient tests. The results of this study indicate that Business Capital has a partially significant effect on the Financial Performance of Culinary MSMEs in Asia Mega Mas Medan with a calculated T-value of 5.221 > T-table of 1.99773. Financial Management has a partially significant effect on the Financial Performance of Culinary MSMEs in Asia Mega Mas Medan with a calculated T-value of 5.730 > T-table of 1.99773. Business Capital and Financial Management have a simultaneously significant effect on the Financial Performance of Culinary MSMEs in Asia Mega Mas Medan with a calculated F-value of 106.449 > F-table of 3.14 and a regression coefficient value of 77.2%.